Pengaplikasian Konsep Mindful Space Terhadap Interior Ruang Kelas Taman Kanak-kanan - Gani, Anastasia Cinthya; Utama, Missheal; Effendi, Andrey Caesar (Prodi Arsitektur Universitas Matana, 2024)
Early childhood is a golden period where support is needed from various parties, one of which is school. But in reality, there are still many educational institutions that have not been able to meet all the needs of children, one of which is in terms of facilities, such as interiors. This discussion highlights the classrooms of Shining Stars Preschool & Kindergarten in South Tangerang as a case study. Through the interior design process, the concept formed is Mindful Space. The main focus of this concept is to create a space where inspiration, creativity and comfort can come together. The design adopts a modern interior style with the use of soft colors that create a comfortable yet fun atmosphere for children. This research uses a qualitative method with an analysis and synthesis approach. The collection of ideas is done through sources such as the internet, books, journals, and direct observation in the field. Thus, this abstract provides an overview of the importance of appropriate and supportive interior design for early childhood in an educational context, with this research as an example of its implementation at Shining Stars Preschool & Kindergarten.